Малосигнальная модель транзистора в разработке СВЧ малошумящих усилителей - Yemtsev, P. A. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A semi-analytical method for determining the parameters of high electron mobility transistors is presented, which requires only data on the transistor’s S-parameters measured over a wide frequency range. The main aspects of model decomposition are described. An example of amplifier construction is given to verify the adequacy of the model.